Engaging older adults with a migration background to explore the usage of digital technologies in coping with dementia - Catharina M. van Leersum; Kornelia E. Konrad; Egbert Siebrand; Zohrah B. Malik; Marjolein E. M. den Ouden; Marloes Bults (Frontiers Media S.A., 2023)
BackgroundCoping with dementia can imply particular challenges for people with a migration background due to diversity in their life course, personal characteristics, and living environment. Some of the services available for people with dementia include digital technologies for care, providing health services, and maintaining or increasing participation, independence, and safety. This study aimed to explore the role of digital technology in coping with dementia in the lives of older adults with a migration background, and the possibilities to engage and collaborate with older adults.MethodsThis study combined a qualitative interview-based approach with citizen science principles in the design and execution of a project studying the use of Anne4Care.Results and discussionParticipants valued that technology should provide health benefits and fit into aspects of their daily lives. Anne4Care was considered helpful in staying independent and connecting to loved ones in their country of birth. The participants needed to learn new competencies to work with the device, and not all had the material prerequisites, such as an internet connection. Still, this learning process was considered purposeful in their life, and the virtual assistant could be integrated into care and daily practices. The involvement of the older adults with dementia as co-researchers made them feel valuable and as equal partners during this research. An important prerequisite for the involvement of older adults with a migration background was existing relations with carers and care organizations.ConclusionDigital care technologies to cope with dementia can become a valuable part of care practices in the lives of older adults with a migration background. Involving older adults in the development of technology, acknowledging their expertise and needs, and working together in short iterations to adapt the technology for their specific needs and situations were experienced as valuable by the researchers, older adults, and care professionals.